2013
DOI: 10.1111/ijn.12187
|View full text |Cite
|
Sign up to set email alerts
|

Health‐promoting lifestyle behaviours in pregnant women in Turkey

Abstract: This study aims to describe the health-promoting lifestyle behaviours of pregnant women. The study was carried out with pregnant women who applied to the polyclinics in different maternity and children hospitals located in Adana, Turkey, between 1 March and 30 May 2009. The data collection tools used in the study were (i) a questionnaire that was used to collect sociodemographic data from the participants and (ii) the Health Promoting Lifestyle Profile II (HPLP II). The results obtained from the study showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
29
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 20 publications
12
29
3
3
Order By: Relevance
“…Stark and Brinkley did not find any relationship between pregnancy age and behaviors scores (26). In terms of number of pregnancies, some studies found no relationship between the number of pregnancies and the scores of health-promoting behaviors (2,11,24). Gharaibeh et al in Turkey explained that multiparous women earned higher scores in the self-actualization dimension compared to primiparous women (5).…”
Section: Observational Studiesmentioning
confidence: 93%
See 4 more Smart Citations
“…Stark and Brinkley did not find any relationship between pregnancy age and behaviors scores (26). In terms of number of pregnancies, some studies found no relationship between the number of pregnancies and the scores of health-promoting behaviors (2,11,24). Gharaibeh et al in Turkey explained that multiparous women earned higher scores in the self-actualization dimension compared to primiparous women (5).…”
Section: Observational Studiesmentioning
confidence: 93%
“…According to the scores obtained from the questionnaire (HPLP-II), consisting of 52 items and 6 sub-domains including nutrition, physical activity, spiritual growth, stress management, health responsibility, interpersonal relations (1,11,18), regarding the total score of healthpromoting behaviors, pregnant women's status ranked as medium and low (5,9,11,23). Only the studies conducted in Thailand by Thaewpia and colleagues as well as Onat in turkey reported a better total score (24,25).…”
Section: Observational Studiesmentioning
confidence: 99%
See 3 more Smart Citations